The Position of the Victim in the Law and Procedure of the International Criminal Court - alireza ghasemisaghand (پژوهشهای حقوقی)
The victim is an element whose rights have been violated by committing a crime. Although it seems obvious that the perpetrator of the suffering of crime is the most important element of the criminal justice process, this notion has not always been realized not only in domestic law but also in international criminal law. Despite the neglect of the victim in the documents of the old specialized international criminal courts in the new generation of these courts and especially in the law and procedure of the International Criminal Court, the victim has enjoyed an important position in the preliminary investigation, trial and execution, but the challenges and shortcomings There are some in this regard. Deficiencies that must be judged in terms of important developments in favor of the victims. But one cannot ignore the fact that the Court has greatly curtailed the historic opportunity to grant criminal justice to individuals in the international community against perpetrators of international crimes.